PERSEPSI MASYARAKAT PADA PROGRAM YUK KEEP SMILE (YKS) DI TRANS TV (STUDI DI KEL. TELUK BELITUNG KEC. MERBAU KAB. KEPULAUAN MERANTI) - Azrul Fahmi; Rusmadi Awza (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
The program Fast video television of course there is a process transmission greetings from communicator to audiensnya. Message through the program Fast or television show its inherent value contained value/, the values that television station as an effective communicator tried to can convey to audience or komunikannya. Various kinds of program presented by television stations. They compete to present can program is interesting and liked by many people. One of the mushrooming in Indonesia this program is Fast - Let's keep Smile (YKS) in Trans TV. This research uses qualitative tried to understand and interpret the meaning of an event interaction appearance man in certain situations in the perspectives researchers itself. Technical data collection in a way observation, interview and documentation. Data that was recieved by then processed for reduced, served to produce a general conclusions. Informant in this research method 12 person based on snowbal sampling. While for the investigation validity data therefore use techniques for the extended the inclusion and triangulation.Results of these studies showing a public perception on the performance Fast YKS in Trans TV according to informers interesting and different with entertainment events that are on television stations such as Pesbuker in ANTV and Extravaganza in Trans 7, and YKS willing to accept criticism and suggestions from other people to improve the motivating and Fast YKS since launching until this time less comfort, and the social control in the event this can be seen from the performance of the players who are less influence over children.Keyword : Persepsi Masyarakat, YKS, Program Televisi